PENENTUAN FORMULASI EMPIRIS YANG SESUAI UNTUK MENGESTIMASI KURVA INTENSITAS DURASI FREKUENSI - Harisuseno, Donny; Wahyuni, Sri; Dwirani, Yosie (Jurusan Teknik Pengairan, Fakultas Teknik, Universitas Brawijaya, 2020)
High rainfall intensity will cause large surface runoff and can lead to negative effects. The IDF curve makes it easy to calculate the design flood. The purpose of this study is to determine the empirical method of rainfall intensity and IDF that are suitable for the study location. The methods used are Talbot, Mononobe, Hasper Der Weduwen, and Van Breen. The result of the calculation found that the most suitable method for this location is Talbot Method. The Talbot Method has an Average Deviation of 1.49, an Average Relative Error of 8.64%, and the Average of Nash-Sutcliffe Efficiency Coefficient (NSE) by 0.98. Then the calculations for the validation of the selected method is using a 2-year return period and 5-year return period have the results of an Average Deviation value of 2.22, the Average Relative Error value of 15.11% and the Average of Nash-Sutcliffe Efficiency Coefficient (NSE) by 0.93.